2018
DOI: 10.1590/1983-1447.2017.04.63060
|View full text |Cite
|
Sign up to set email alerts
|

Aplicabilidade da Moral Distress Scale adaptada no cenário da enfermagem em hemato-oncologia

Abstract: This study showed that the adapted Moral Distress Scale is an appropriate instrument for the identification of moral distress in nursing workers in the hemato-oncology area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In other studies, for example in Hamaideh [34], older and more experienced nurses reported fewer moral stressors. Among nurses, lower income [34] and higher educational levels were associated with higher frequency and greater intensity of stressors [33,34]. In terms of coping behaviors, using problem-solving strategies was associated with experiencing fewer moral stressors [58].…”
Section: Vulnerability Indicators For Moral Distress and Moral Injury In Healthcare Workersmentioning
confidence: 93%
See 4 more Smart Citations
“…In other studies, for example in Hamaideh [34], older and more experienced nurses reported fewer moral stressors. Among nurses, lower income [34] and higher educational levels were associated with higher frequency and greater intensity of stressors [33,34]. In terms of coping behaviors, using problem-solving strategies was associated with experiencing fewer moral stressors [58].…”
Section: Vulnerability Indicators For Moral Distress and Moral Injury In Healthcare Workersmentioning
confidence: 93%
“…Regarding work experience, there are contradictory results. For example, in Shoorideh et al [57] and Fruet et al [33], higher age and longer work experience were associated with higher chances of experiencing moral stressors. In other studies, for example in Hamaideh [34], older and more experienced nurses reported fewer moral stressors.…”
Section: Vulnerability Indicators For Moral Distress and Moral Injury In Healthcare Workersmentioning
confidence: 93%
See 3 more Smart Citations